THE EFFECT OF AUTOGENIC RELAXATION ON BLOOD GLUCOSE LEVELS IN TYPE 2 DIABETES MELLITUS: SYSTEMATIC REVIEW - Amalia Rahma; Popi Sopiah; Rafika Rosyda (Buletin Veteriner Udayana, 2024)
Type 2 Diabetes Mellitus (DM) is a disorder in the body due to high blood sugar levels resulting in cell insensitivity to insulin. The high incidence of DM cases and the impact that can be caused both physically and psychologically make sufferers need to understand DM treatment with the aim of reducing symptoms and preventing complications or death. One non-pharmacological efforts that can be made is autogenic relaxation therapy. The aim of this research is to review and synthesise the findings of existing research on the effect of autogenic relaxation on blood glucose levels in people with type 2 diabetes mellitus. The research method used is systematic review. The article search used 3 databases, namely Google Scholar, Cochrane Library, and PUBMED, so that 14 relevant articles were obtained for further review. The results of the 14 articles showed that autogenic relaxation is one of the nonpharmacological therapies that can reduce blood glucose levels in people with type 2 diabetes mellitus. The conclusion in this study is that there is an effect of providing autogenic relaxation on blood glucose levels, with decrease of about 20 mg/dl to 100 mg/dl. It is hoped that autogenic relaxation can be used as an alternative to reduce KGD and avoid complications in people witH DM in the family environment and health facilities.